Penerapan dan Evaluasi Strategi Manajemen Risiko Keuangan pada UMKM (Studi Kasus Batik Ronggomukti Sidomukti Kecamatan Kraksaan Kabupaten Probolinggo) - Imroatul Maghfiroh; Mamluatun Ni’mah; Waqi’atul Aqidah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study investigates the implementation and evaluation of financial risk management strategies at Batik Ronggomukti, a creative micro, small, and medium enterprise (MSME) located in Kraksaan District, Probolinggo. The research highligh key financial risk faced by the enterprise, including raw material price volatility, market uncertainty, and limited working capital. Employing a qualitative case study approach, data were collected through in-depth interviews and direct field observations. The findings reveal that Batik Ronggomukti adopts practical and contextually adaptive risk management strategies, such as product diversification to reduce market dependency, manual financial record-keeping for monitoring cash flows, cost efficiency in production processes, and partnership-based financing to avoid high-interest loans. These approaches have contributed to improved operational performance, enhanced cash flows stability, and stronger business resilience against external shocks. However, the current risk management system remains largely informal, with no standardized documentation or quantitative analysis to support decision-making. Evaluation methods are still based on intuition and personal experience, lacking measurable indicators to assess effectiveness. This indicates the need for formal training and the adoption of digital financial tools to strengthen managerial capabilities and risk mitigation. The study concludes by recommending institutional support and collaboration ith government bodies or academic institutions to promote a more sustainable and structured financial risk management framework for MSMEs, ensuring their long-term viability in a dynamic economic environment.